Uso de redes virtuales en adolescentes de contextos vulnerables: comportamiento agresivo y estrategias de afrontamiento - Lacunza, Ana Betina (2022)
Digital technologies have produced new ways of communication among adolescents, which can be both healthy and dysfunctional. The purpose of this study was to identify frequent uses of social networks and coping strategies for aggressive practice. The participants were 243 students in situation of vulnerability from S. M. de Tucumán (Argentina). More than 70% informed healthy uses, 14% recognised themselves as having cyber aggressive behaviour and 23% as being cyber victims. An analysis by Anova and Bonferroni showed that this group indicated the use of nonproductive strategies such as Self-blaming, Wishful Thinking, Not coping, Keeping to self, Worrying and Tension Reduction. Data confirm a higher psychological vulnerability of adolescents who are victims of cyber aggression to face stressful situations.